Evaluation of volatile aroma compounds from Chinese wild grape berries by headspace-SPME with GC-MS - RAHMAN,Faiz Ur (2022)
Abstract Evaluation of volatile aroma compounds from Chinese wild grape species aimed to explore new grape species via fruit aroma. In this study, the volatile organic compounds (VOCs) from ten grape cultivars belonging to nine different grape species were detected, by using headspace solid-phase microextraction with GC-MS. Chinese wild grape species were studied along with table grape (Muscat Hamburg, Concord) and wine grape (Cabernet Sauvignon) cultivars belonging to different origins. Total forty-five volatile compounds were detected, upon which several VOCs including pentanoic acid, cyclobutyl ester, maltol, (+)-neoisomenthol, and 8-methyloctahydrocoumarin were detected in Chinese wild grapes that have not been detected in other Vitis species. The results revealed that C6 volatile compounds were pre-dominant VOCs. Esters were found abundant in V. labrusca (Concord) and terpenoids were dominant in V. vinafera (Hamburg Muscat). The principal component analysis showed that Chinese wild grape cultivars V. yeshanensis, V. facifolia, V. davidii, V. betulifolia V. heyneana, V. amurensis and V. adenoclada are correlated with wine grape cultivar ‘Cabernet Sauvignon’, while table grape cultivars are distributed separately. These results can provide a reference for the utilization of new germplasm for specific purposes.